A descriptive study on the global self-esteem levels of the UP Dental Proper Students, A.Y. 2006-2007 - Gillesania, Lorelyn V.
It is essential for students to develop appropriate professional attitudes towards themselves and their work, in addition to acquiring dental knowledge and technical skills. One of the valued attitudes of a competent dentist is the possession of an acceptable level of self-esteem which is described as one's overall sense of value or worth (Rosenberg, 1965). A limited number of studies about self esteem have been done on the Filipino population, and none on students of the University of the Philippines Manila College of Dentistry (UPCD). This study aims to describe the global self-esteem levels of UP Dental proper students as of A.Y. 2006=2007. The results of this study will establish the backbone for any continuation on the exploratory study on the self-esteem of the respondents. It was the intention of hte researchers of this study to do total enumeration of the target population. However, due to time constraints and lack of means to contact certain students during data collection, only 162 or 88% of 185 UP dental proper students were able to participate in the study. The cut-off high and low self esteem levels used in this study is the median self-esteem score of all the respondents. The results of the study show that in the gender category, both male and female groups have high self-esteem levels. In the year level category, 2nd year, 3rd year, and resident groups have low self-esteem levels. Based on academic performance, 1st year and resident group with failed subjects, 2nd year with and without failed subjects, and 3rd year group without failed subjects also have low self-esteem levels, Lastly, for the SES category, the groups that have high self-esteem levels are Class A, Class C, and Class E.